1983
DOI: 10.1177/001872088302500102
|View full text |Cite
|
Sign up to set email alerts
|

Capacity Demands in Short-Term Memory for Synthetic and .Natural Speech

Abstract: Three experiments were performed that compared recall for synthetic and natural lists of monosyllabic words. In the first experiment, presentation intervals of 1, 2, and 5 s per word were used. Although free recall was consistently poorer overall for the synthetic lists at all presentation rates, the decrement for synthetic stimuli did not increase differentially with faster rates. In a second experiment, zero, three, and six digits were presented visually for retention prior to free recall of each spoken word… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
83
2

Year Published

1985
1985
2008
2008

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 148 publications
(94 citation statements)
references
References 15 publications
9
83
2
Order By: Relevance
“…In another experiment, Luce et al (1983) presented subjects with lists of 10 natural words or 10 synthetic words to be memorized and recalled in serial order. Overall, natural words were recalled better than synthetic words.…”
Section: Perceptual Evaluation Of Synthetic Speechmentioning
confidence: 99%
“…In another experiment, Luce et al (1983) presented subjects with lists of 10 natural words or 10 synthetic words to be memorized and recalled in serial order. Overall, natural words were recalled better than synthetic words.…”
Section: Perceptual Evaluation Of Synthetic Speechmentioning
confidence: 99%
“…It is not immediately obvious to us how one would account for these findings, given the results of an earlier study by Luce, Feustel & Pisoni (1983), which showed increased error rates in serial recall when capacity demands of the task were increased. We do not know of any current theory of human information processing or language comprehension that would predict the results observed by Moody & Joost.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…When subjects listened to more difficult information in some passages, differences in performance between the natural speech group and the synthetic speech group were not observed. However, when the comprehension materials were easy, significant differences between the natural and synthetic speech groups emerged.It is not immediately obvious to us how one would account for these findings, given the results of an earlier study by Luce, Feustel & Pisoni (1983), which showed increased error rates in serial recall when capacity demands of the task were increased. We do not know of any current theory of human information processing or language comprehension that would predict the results observed by Moody & Joost.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We also carried out a series of exper iments to determine the effects of encoding synthetic speech on working memory and rehearsal processes [LFP83]. Subjects were given two different lists of items to remember: The first list consisted of a set of digits visually presented on a CRT, screen; the second list consisted of a set of ten natural words or ten synthetic wordi.…”
Section: Capacity Demands In Speech Perceptionmentioning
confidence: 99%